Preference for Life Partners in Early Adult Women: The Role of Self-Esteem and Father's Involvement? - Novi Safitri; Khoiriyah Ulfa; Mustamira Sofa Salsabila (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2024)
Fathers have a big influence on rational decision making for early adult women. There is a positive relationship between the influence of father involvement on early adult women's decision making. Women who are close to their fathers tend to have the same preferences as their fathers in choosing a life partner. The aim of this study was to examine the relationship between self-esteem and father involvement with life partner selection preferences in early adult women. Purposive sampling technique was used for sampling in this study and 201 subjects were involved. Data collection was carried out using the Partner Selection Scale, Self-Esteem Scale, and Father's Involvement Scale with reliability of 0.705, 0.940, and 0.942 respectively. The data analysis method used in this research is multiple regression analysis using JASP for Windows software. The results of the research show the coefficient of determination (r2) = 0.788, F count of 366.978, and a significance level of 0.001 (P > 0.001) so it can be concluded that self-esteem and father involvement have an influence on the preference for choosing a life partner by 78.8%.Ayah mempunyai pengaruh yang besar terhadap pengambilan keputusan rasional bagi wanita dewasa awal. Terdapat hubungan positif antara pengaruh keterlibatan ayah dengan pengambilan keputusan pada wanita dewasa awal. Wanita yang dekat dengan ayahnya cenderung memiliki preferensi yang sama dengan ayahnya dalam memilih pasangan hidup. Tujuan dari penelitian ini adalah untuk menguji hubungan antara harga diri dan keterlibatan ayah dengan preferensi pemilihan pasangan hidup pada wanita dewasa awal. Teknik purposive sampling digunakan untuk pengambilan sampel pada penelitian ini dan 201 subjek dilibatkan. Pengumpulan data dilakukan dengan menggunakan Skala Pemilihan Pasangan, Skala Harga Diri, dan Skala Keterlibatan Ayah dengan reliabilitas masing-masing sebesar 0,705, 0,940, dan 0,942. Metode analisis data yang digunakan dalam penelitian ini adalah analisis regresi berganda dengan menggunakan software JASP for Windows. Hasil penelitian menunjukkan koefisien determinasi (r2) = 0,788, F hitung sebesar 366,978, dan taraf signifikansi 0,001 (P > 0.001) sehingga dapat disimpulkan bahwa harga diri dan keterlibatan ayah memiliki pengaruh terhadap preferensi pemilihan pasangan hidup sebesar 78.8%.